2007
DOI: 10.1111/j.1467-8624.2007.01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Training Parents to Mediate Sibling Disputes Affects Children's Negotiation and Conflict Understanding

Abstract: The effects of training parents to use formal mediation procedures in sibling disputes were examined in 48 families with 5- to 10-years-old children, randomly assigned to mediation and control conditions. Children whose parents were trained in mediation were compared with those whose parents intervened normally. Parents reported that children used more constructive conflict resolution strategies, compromised more often, and controlled the outcomes of conflicts more often in mediation families than in control f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 58 publications
4
64
0
3
Order By: Relevance
“…Besides communicating this message directly to parents during pediatric visits, another avenue to disseminate this message would be to have popular parent education programs (eg, Triple P Positive Parenting Program) to include a greater focus on sibling aggression and successful mediation of sibling conflicts. 25 An important next step is to gather longitudinal data to further examine the implications of various patterns of sibling aggression experiences for mental health and whether these patterns vary by birth order and gender.…”
Section: Discussionmentioning
confidence: 99%
“…Besides communicating this message directly to parents during pediatric visits, another avenue to disseminate this message would be to have popular parent education programs (eg, Triple P Positive Parenting Program) to include a greater focus on sibling aggression and successful mediation of sibling conflicts. 25 An important next step is to gather longitudinal data to further examine the implications of various patterns of sibling aggression experiences for mental health and whether these patterns vary by birth order and gender.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the findings provide partial support for previous research that has demonstrated a parenting program can improve sibling relationship functioning (Feinberg et al, 2013;Ross & Lazinski, 2014). The findings add weight to the body of research that showed that the extent to which parents involve themselves in their children's disputes is likely to influence their children's sibling relationships (Brody, 1998;Smith & Ross, 2007). The findings also support the claims made by Tucker et al (2013) and Wolke et al (2015) that parenting programs may be a useful tool in promoting improved relationships among siblings.…”
Section: Discussionsupporting
confidence: 60%
“…Previous research identified that parents are key players in shaping the quality of their children's sibling relationships (Ross & Lazinski, 2014). The extent to which parents involve themselves in their children's quarrels, and the strategies they use when doing so, are highly predictive of sibling relationship outcomes (Brody, 1998;Smith & Ross, 2007 (Kramer, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A contrasting approach that involves power assertion has been seen as more singly and immediately aimed toward eliminating conflict, and entails greater use of disciplinary tactics and consequences, such as punishment, threats, or withholding privileges. Despite the obvious differences between these types of approaches, both power assertion (Allison & Allison, 1971;Furman & McQuaid, 1992;Olson & Roberts, 1987) and child-centered methods (Dunn & Munn, 1986;Kramer, 2004;Smith & Ross, 2007) have at times been found effective, leaving little consensus as to the optimal method for reducing conflict. Perhaps due to these seemingly contradictory results and despite the fact that parents are of the opinion that intervention is more effective than nonintervention, the tactic that is most typically adopted by parents of squabbling siblings is nonintervention.…”
Section: Contextual Determinants Of Adults' Perceptions Of Child Miscmentioning
confidence: 99%